Experiências de desenvolvimento territorial : a questão do PROINF e da gestão social no território da cidadania da bacia leiteira/AL - Silva, Jislaine Lima da (2017)
Based on the need to promote actions to fight poverty and inequalities in Brazilian countryside, the State, based on public policies of territorial approach, has been promoting actions to sustain family agriculture and to boost rural areas, so that civil society and public authority assume an active role in this process. The rural territorial development policy emerged in Brazil from the Rural Territories programme in 2003, being implemented in several Brazilian territories, as in the case of the Citizenship Territory of Bacia Leiteira (CTBL) in the state of Alagoas. The territory consists of 11 municipalities, which will be analyzed in the present work from the perspective of territorial development and analysis of PROINF, which is created with the objective of promoting resources for sustainable rural development projects within the territorial approach. Analyzing the economic dynamism of PROINF in the Territory of Bacia Leiteira in a spatial perspective and the importance of social management: implications, advances and contradictions in the Territorial Development policy, constitute the general objective of the research. In order to create the research are used the territorial category and the concepts of rural development, territorial development, social management and Infrastructure and Services Project in Rural Territories (ISPRT). Being used an empircal analytical methods, quantitative and qualitative, which analyse the general aspects and reflect the information of reality, in this regard, were carried out the following methodological procedures: survey review bibliography, search and analysis of secondary data, semi-open interviews with social actors from the Collegiate and field work analyse, by sample, projects of the Infrastructure and Services Project in Rural Territories (ISPRT) from 2003 to 2014. Due to the conjuncture established by the rural territorial development policy, arises the necessity to make more expressive study of the territory of Bacia Leiteira as a case study, knowing that one of the objectives of the Citizenship Territories is to integrate the spaces into a common ideal, in the search for rural development in the municipalities, among them the Infrastructure and Services Project in Rural Territories (ISPRT) and its socio-spatial unfolding. In short, the territorial policy has been allowing the strengthening and inclusion of several social segments that have marginalized. In the Citizenship Territory of Bacia Leiteira (CTBL), the (ISPRT) has brought positive results and is well evaluated by the social actors of the territory and even with logistic problems have managed to make a good articulation with the territorial policy. As regards to social management, it is still necessary that social subjects understand their importance and perform it.